Sleep disorders in chronic pain and its neurochemical mechanisms: a narrative review - Duo, Lan; Yu, Xintong; Hu, Ruihan; Duan, Xiping; Zhou, Jia; Wang, Ke (Frontiers in Psychiatry, 2023)
Chronic pain (CP) is a prevalent problem, and more than half of patients with CP have sleep disorders. CP comorbidity with sleep disorders imposes immense suffering and seriously affects the patient’s quality of life, which is a challenging issue encountered by clinicians. Although the reciprocal interactions between pain and sleep have been studied to some degree, there is still a lack of awareness and comprehensive description of CP comorbidity with sleep disorders. In this narrative review article, we summarize the current knowledge about the present estimates of the prevalence of comorbid sleep disorders in CP patients, sleep detection methods, sleep characterization in CP, and the effect of sleep disorders on CP and current therapies. We also summarize current knowledge of the neurochemical mechanisms of CP comorbidity with sleep disorders. In conclusion, insufficient attention has been paid to the role of sleep disorders in CP patients, and CP patients should be screened for sleep disorders in the clinic. Special attention should be given to a possible risk of drug-drug interaction when using two types of drugs targeting pain and sleep simultaneously. The current insight into the neurobiological mechanisms underlying CP comorbidity with sleep disorders is still rather limited.